Evaluation of antidiabetic properties of Momordica charantia in streptozotocin induced diabetic rats using metabolomics approach - Perumal, Vikneswari; Khoo, Wei Chi; Abdul Hamid, Azizah; Ismail, Amin; Shaari, Khozirah; Murugesu, Suganya; Abas, Faridah; Ismail, Intan Safinar; Lajis, Nurdin; Mushtaq, Mian Yahya; Khatib, Alfi (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Momordica charantia, also known as bitter melon or ‘peria katak’ in Malaysia, is a member of the family Cucurbitaceae. Bitter melon is an excellent source of vitamins and minerals that made it extensively nutritious. Moreover, the seed, fruit and leave of the plant contain bioactive compounds with a wide range of biological activities that have been used in traditional medicines in the treatment of several diseases, including inflammation, infections, obesity and diabetes. The aim of this study was to evaluate changes in urinary metabolite profile of the normal, streptozotocin-induced type 1 diabetes and M. charantia treated diabetic rats using proton nuclear magnetic resonance (1H-NMR) -based metabolomics profiling. Study had been carried out by inducing diabetes in the rats through injection of streptozotocin, which exhibited type 1 diabetes. M. charantia extract (100 and 200 mg/kg body weight) was administrated to the streptozotocin-induced diabetic rats for one week. Blood glucose level after administration was measured to examine hypoglycemic effect of the extract. The results obtained indicated that M. charantia was effective in lowering blood glucose level of the diabetic rats. The loading plot of Partial Least Square (PLS) component 1 showed that diabetic rats had increased levels of lactate and glucose in urine whereas normal and the extract treated diabetic rats had higher levels of succinate, creatine, creatinine, urea and phenylacetylglycine in urine. While the loading plot of PLS component 2 showed a higher levels of succinate, citrate, creatine, creatinine, sugars, and hippurate in urine of normal rat compared to the extract treated diabetic rat. Administration of M. charantia extract was found to be able to regulate the altered metabolic processes. Thus, it could be potentially used to treat the diabetic patients.